2015
DOI: 10.1001/jama.2015.1163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scattered-Site Housing Using Rent Supplements and Intensive Case Management on Housing Stability Among Homeless Adults With Mental Illness

Abstract: isrctn.org Identifier: ISRCTN42520374.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
235
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(260 citation statements)
references
References 35 publications
13
235
2
10
Order By: Relevance
“…We identified a total of four studies that used an RCT design to examine the effects of PSH on health services utilization and associated costs. Overall, these studies found that, relative to control groups, the treated groups experienced a decrease in hospital days by 23 to 29 percent and a decline in the number of ER visits by 24 to 33 percent (see Basu et al, 2012;Sadowski et al, 2009;Stergiopoulos et al, 2015). Also, Basu et al (2012) found that the treated group used substance-use residential treatment significantly less frequently than the control group that was subject to a non-Housing First approach.…”
Section: Studies Using Randomized Controlled Trialsmentioning
confidence: 98%
See 2 more Smart Citations
“…We identified a total of four studies that used an RCT design to examine the effects of PSH on health services utilization and associated costs. Overall, these studies found that, relative to control groups, the treated groups experienced a decrease in hospital days by 23 to 29 percent and a decline in the number of ER visits by 24 to 33 percent (see Basu et al, 2012;Sadowski et al, 2009;Stergiopoulos et al, 2015). Also, Basu et al (2012) found that the treated group used substance-use residential treatment significantly less frequently than the control group that was subject to a non-Housing First approach.…”
Section: Studies Using Randomized Controlled Trialsmentioning
confidence: 98%
“…For example, a PSH program that targeted individuals experiencing homelessness and serious mental illness demonstrated a 95-percent reduction of postintervention public service costs among those who were housed (Culhane, Metraux, and Hadley, 2002); a program targeting individuals who experienced chronic homelessness, had severe alcohol use disorders, and were high users of crisis centers and hospitals showed a cost reduction of 53 percent (Larimer et al, 2009). However, programs that have enrolled individuals with less serious health conditions have yielded more modest cost reductions (Stergiopoulos et al, 2015). Moreover, smaller (partial) program cost offsets tend to be found in earlier phases of the program (Bamberger and Dobbins, 2014;Basu et al, 2012;Brown et al, 2012;Culhane, Metraux, and Hadley, 2002;Flaming, Burns, and Matsunaga, 2009;Larimer et al, 2009;Mondello et al, 2007;Reaser and Mauerman, 2015;Sadowski et al, 2009;Seligson et al, 2013;Stergiopoulos et al, 2015;Thomas et al, 2014;Toros, Stevens, and Moreno, 2012;Tsemberis, Gulcur, and Nakae, 2004;Wright et al, 2016).…”
Section: Service Utilization and Costs Among Populations Experiencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials have found housing stability and retention for HF participants to be between 73% and 80% as compared to usual care, which, depending on the study consisted of access to existing forms of housing assistance and support in the community or programs following a "treatment first" approach that made access to permanent housing conditional on successful treatment adherence, had rates of approximately 30%. 2,3 Furthermore, there has been remarkable consistency across evaluations of HF programs. In a review of eight published studies of Housing First that reported on housing retention and stability during periods that ranged from 1 to 5 years, rates varied from 73% to 88%.…”
Section: Introductionmentioning
confidence: 99%
“…The trial protocol is provided in detail in Goering et al, 15 and 24-month outcomes are reported elsewhere. 16,17 The cities differed in rental market conditions, so we knew that finding quality rental units would be more challenging in some sites. We also wanted to ensure that housing units procured in the private market with rent supplements from a publicly funded program were of acceptable quality.…”
Section: Introductionmentioning
confidence: 99%